Pengelolaan Media Sosial YouTube Kementerian Sekretariat Negara RI Sebagai Media Informasi dan Publikasi - Robiana, Raden Daffa Naridza; Anugrah, Dadan; Rusmulyadi, Rusmulyadi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the implementation of Kementerian Sekretariat Negara RI YouTube social media management activities at the share, optimize, manage and engage stages as an information and publication medium. The Circular Model of SoMe for Social Communication is used in this study, along with a constructivist paradigm and an interpretive qualitative approach. Descriptive research methods are supported by data collection through observation, interviews, and documentation. The results of this study indicate that YouTube Kementerian Sekretariat Negara RI as an information and publication medium is used for disseminating information and publications by participating, connecting, building trust, listening to input, taking part in authentic communication, monitoring, interactive communication, influencer speakers up to audience outreach and determination.